Clinical and psychopathological features of patients with type II diabetes mellitus - Kondratenko , A. (Journal of Education, Health and Sport, 2021)
Today, type II diabetes mellitus (T2DM) is considered to be the most important nosological cause of decreased cognitive functions. A number of studies have found that hyperglycemia and duration of diabetes are associated with cognitive deficits, with the prevalence of cognitive impairment in type 2 diabetes mellitus being 20% in men and 18% in women over 60 years of age. To achieve this goal, it was conducted a comprehensive clinical-psychopathological and psychodiagnostic examination of 82 patients with moderate type 2 diabetes mellitus (46 women and 36 men) aged 35.9±10.1 years in accordance with the principles of bioethics and deontology. The mean duration of diabetes was 7.9±5.2 years. The severity of diabetes in most cases was defined as moderate (84.1%), and in 15.9% of cases corresponded to severe. 30.2% of patients used insulin as a basic hypoglycemic therapy, 69.8% - tablets. According to the analysis of the emotional state of patients with T2DM were characterized by complaints of low, depressed mood (69.5% of examined patients), uncontrolled emotional reactions (46.2%), feelings of anxiety, constant internal tension (44.7%), paresthesias (29.1%), sleep-wake cycle disorders (56.2%), general weakness, lethargy and fatigue (58.2%), fatigue (90.0%), frequent mood swings, with a predominance of decreased mood background (23.3%), emotional lability with excessive vulnerability and sensitivity (16.6%), irritability (16.6%). The clinical and psychopathological structure of emotional disorders is represented by anxious (43.4%), depressive (26.6%), astheno-hypochondriac (19.8%), hysteroform (10.2%) syndromes. Clinical examination of patients with DM showed that more often (in 95.0% of cases) in patients with T2DM there is a decrease in memory of auditory and visual modality, impaired intellectual abilities, slow thinking, lack of attention and information processing.